University students' perceptions of airborne infection control: exploratory study using Q methodology - Seonhye Lee; Hyun Jin Kim; Chang Heon Cheong (BMC, 2021)
Abstract Background International cooperation for infection control is important to prevent global pandemics. University students were difficult groups to manage of infection control measures. They often had overconfidence to their health, ineffective personal hygiene, and active social activities. Their misperceptions and inappropriate preventive behaviors increase the infection risks to university and community. Understanding university students' perceptions of airborne infection management will contribute to the establishment of relevant policies and health education programs. Method This study explored subjective perceptions of airborne infection among university students in South Korea using Q-methodology. Forty university students representing different majors ranked a set of 33 statements reflecting their perceptions of airborne infection. They sorted the statements into a distribution on seven scales ranging from "strongly disagree" to "strongly agree." Collected data were analyzed by the PC-QUANL program. The subjective perception types were extracted by using the principal component analysis. Results Four type are derived regardingperception of airborne infection: Type I (Government responsibility), Type II (Personal responsibility in self-management), Type III (Strict external management) and Type IV (Comprehensive countermeasures management). Thesefour types accounted for 45.6% of the total variance, and the individual contributions of Types I, II, III, and IV were 27.7, 7.6, 6.2, and 4.1%, respectively. Conclusion The major contribution of this study is to clarify university students' perceptions of airborne infection. These findings can be used in formulating effective strategies for health education, media reporting, and public health policy to improve airborne infection management.